Factors contributing to energy performance of school buildings: EPC analysis and building simulations - Wang, Chujun; Yasin, Shukri (My University, 2021)
The buildings and construction sector account for 40% of the global energy consumption and CO2 emission. School buildings have potential of reducing energy consumption. The energy performance certificate is a document that aims to help to reduce consumption and tackle emissions. The aim of this thesis is to evaluate the main factors contributing to the energy performance of a sample of school buildings in Gothenburg, Sweden. This was conducted through EPC analysis and the factors that contributing to the energy performance were evaluated. Two schools were selected and modeled in the software IDA ICE for detailed evaluation of differentiating characteristics. Moreover, a sensitivity analysis was further constructed to evaluate main factors affecting energy use and finding the reason for the divergence in performance. The significant correlation found in the statistical analysis of the EPCs was that newer schools had lower heating use intensity and total energy performance. This is due to stricter regulations and heat recovery system installations. Weak correlations found was electricity use intensity increasing with the construction year which is probably due to having electricity demanding mechanical ventilation systems in newer buildings.All meters decreased with area, and this is thought to be due to larger schools having different use thereby having lower intensity of energy use. The difference in surface to volume ratio could possibly explain 73% of the gap between the schools envelope heat losses; and for the difference in window U-value it could explain 22% of heating use intensity gap. The sensitivity analysis resulted in a ranking list for both schools where it could be seen that the most influential factors according to the model of the schools are heat recovery efficiency, temperature setpoint, window U-value, SFP and ventilation flow dimensions. The heat recovery efficiency is the most interesting factor since it is unknown for the energy use intense school and is low for the other school. Based on the analysis of the school buildings, these recommendations can be stated, higher heat recovery efficiency, energy efficient windows, better fans with lower SFP, balancing of ventilation system and taking compactness into consideration at the design phase.
Keywords: Energy performance certificate (EPC) school buildings; School buildings energy use; Building energy simulation (BES)